Widespread epigenetic abnormalities suggest a broad DNA methylation erasure defect in abnormal human sperm. - Sahar Houshdaran (Public Library of Science (PLoS), 2007)
Background Male-factor infertility is a common condition, and etiology is unknown for a high proportion of cases. Abnormal epigenetic programming of the germline is proposed as a possible mechanism compromising spermatogenesis of some men currently diagnosed with idiopathic infertility. During germ cell maturation and gametogenesis, cells of the germ line undergo extensive epigenetic reprogramming. This process involves widespread erasure of somatic-like patterns of DNA methylation followed by establishment of sex-specific patterns by de novo DNA methylation. Incomplete reprogramming of the male germ line could, in theory, result in both altered sperm DNA methylation and compromised spermatogenesis. Methodology/principal finding We determined concentration, motility and morphology of sperm in semen samples collected by male members of couples attending an infertility clinic. Using MethyLight and Illumina assays we measured methylation of DNA isolated from purified sperm from the same samples. Methylation at numerous sequences was elevated in DNA from poor quality sperm. Conclusions This is the first report of a broad epigenetic defect associated with abnormal semen parameters. Our results suggest that the underlying mechanism for these epigenetic changes may be improper erasure of DNA methylation during epigenetic reprogramming of the male germ line.